ASSESSMENT OF INNOVATIVE EFFECT OF NATIONAL AND REGIONAL ECONOMICS - Kasim N. Yusupov; Rustem R. Akhunov; Yuliya S. Toktamysheva (Статистика и экономика, 2016)
This paper presents the results of the analysis of the effectiveness of innovation by the method of resulted expenses. The results of modernization are predicted by information of production of the main economic branches. The research has been conducted on the basis of the input-output balance in System of National Account and in Balance of the National Economy.